Strategi Penguatan Profil Pelajar Pancasila Dimensi Berkebhinekaan Global Di Sekolah Dasar - Nafiah Nur Shofia Rohmah; Markhamah; Sabar Narimo; Choiriyah Widyasari (Jurnal Elementaria Edukasia, 2023)
The Pancasila Student Profile has six dimensions: faith and devotion to God, diversity in the world, independence, mutual cooperation, critical thinking, and creativity. Global diversity is an appreciation of diversity that comes from the awareness that Indonesia is a big nation with various ethnicities, traditions and cultures that accompany it. The purpose of this study is to explain how SDIT Nur Hidayah Surakarta has strengthened the global diversity aspect of the Pancasila Student Profile. The phenomenological research method is used in the qualitative research methodology. The results of research conducted at SDIT Nur Hidayah Surakarta regarding the strategy of strengthening the profile of Pancasila students with the dimensions of global performance diversity that the strategy is implemented by integrating it into learning activities such as intra-curricular activities and then packaging it into project activities to strengthen student profiles such as introducing Pancasila Teachers using habituation exercises to help students develop a stronger appreciation of cultural diversity around the world. The teachers set an example by not picking friends at school, getting along with everyone in the school community regardless of skin color, religion, or other characteristics, setting an example of tolerance, and carrying out the flag ceremony every Monday, and respecting differences of opinion, can be seen as strengthening the profile of Pancasila students with global diversity dimensions at SDIT Nur Hidayah Surakarta Keywords: Elementary school ; Global Diversity ; Pancasila Student Profile